1981
DOI: 10.1159/000198570
|View full text |Cite
|
Sign up to set email alerts
|

Action of Secretagogues on Amylase Release from Dog Pancreatic Acini

Abstract: This work describes a new preparation of dog pancreatic acini which were used to study amylase release in response to various secretagogues. Neither secretin nor vasoactive intestinal peptide stimulated amylase release from acini. Caerulein, carbachol and human synthetic gastrin G17 stimulated amylase release with the same efficacy, but with different potencies. Bombesin nonapeptide did not show any evidence of a direct stimulatory effect on amylase release. These species-related peculiarities stress the neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…The contribution of endogenous CCK to the action of bombesin and related peptides seems to be relatively smaller in dogs than in cats, because in this species CCK receptor antagonist only partially reduced bombesininduced pancreatic secretion [24,25], while in cats, as demonstrated in this study, this antagonist resulted in almost complete sup pression of the pancreatic secretory response to GRP. The mediation of CCK in the ca nine pancreatic secretion induced by bombe sin is also supported by the previous finding that bombesin, unlike CCK, is unable to stimulate amylase release from the dispersed canine pancreatic acini [26], It is of interest that in rats, but not in other species, bombe sin stimulates exocrine pancreas mainly by direct action on acinar cells and not through the release of CCK and gastrin or via cholin ergic pathways. This is supported by obser vations showing that the stimulation of pan creatic protein or enzyme secretion induced by bombesin cannot be suppressed by pep tidergic or nonpeptidergic antagonists of CCK receptors either in vivo or in vitro [ 19,27,28], More detailed studies confirmed the presence of specific and separate receptors for CCK and bombesin-like peptides in the rat pancreas [2].…”
Section: Discussionsupporting
confidence: 59%
“…The contribution of endogenous CCK to the action of bombesin and related peptides seems to be relatively smaller in dogs than in cats, because in this species CCK receptor antagonist only partially reduced bombesininduced pancreatic secretion [24,25], while in cats, as demonstrated in this study, this antagonist resulted in almost complete sup pression of the pancreatic secretory response to GRP. The mediation of CCK in the ca nine pancreatic secretion induced by bombe sin is also supported by the previous finding that bombesin, unlike CCK, is unable to stimulate amylase release from the dispersed canine pancreatic acini [26], It is of interest that in rats, but not in other species, bombe sin stimulates exocrine pancreas mainly by direct action on acinar cells and not through the release of CCK and gastrin or via cholin ergic pathways. This is supported by obser vations showing that the stimulation of pan creatic protein or enzyme secretion induced by bombesin cannot be suppressed by pep tidergic or nonpeptidergic antagonists of CCK receptors either in vivo or in vitro [ 19,27,28], More detailed studies confirmed the presence of specific and separate receptors for CCK and bombesin-like peptides in the rat pancreas [2].…”
Section: Discussionsupporting
confidence: 59%
“…In vitro studies have provided conflicting results. Bombesin, in fact, stimu lates amylase release from rat [11,21], guinea pig [12], mouse [11] and human [29] pancreatic acini, whereas it was ineffective in the same dog preparation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Little difference exists between species regarding the sensitiv ity to secretagogues, such as cerulein, gastrin or carbachol, which was slightly lower in dog than in rodents. We have reported [1,2] that secretin and VIP had no stimulatory effect on enzyme secretion in dog acini; a similar result has been obtained in dog pancreatic frag ments [14], while these peptides stimulated amylase release from pancreatic acini in ro dents [15,16], The lack of response was not due to an impairment in the peptide prepara tion, since their biological activity was tested during this work on guinea-pig pancreas (stimulation of amylase secretion could be detected at 3• 10 -11 M VIP and 1 -10 -8 M secretin) and the molecular structure was controlled by high performance liquid chro matography. This lack of stimulatory effect on enzyme secretion does not imply that dog pancreatic acini do not possess receptors for VIP or secretin, since these two peptides induced in our model an accumulation of cel lular cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously [1,2] that, contrary to other species, in dog dispersed acini, secretin and vasoactive intestinal pep tide (VIP) neither stimulate amylase release nor potentiate the action of other secretagogues such as cerulein. In guinea-pig acini, potentiation among pancreatic secretagogues occurs with the combination of a secretagogue that causes release of cellular calcium (CCK analogues, cholinergic agents, etc.)…”
mentioning
confidence: 98%